Efektivitas Klausul Kontrak pada Hubungan Bisnis antara UMKM dan Mitra Usaha di Indonesia - Wardoyo, Heru; Budimah, Budimah (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
This study analyzes how effectively contract clauses in business relationships between MSMEs and their partners ensure fair legal protection for MSMEs. It also identifies factors behind MSMEs’ weak bargaining position in partnership agreements and evaluates the role and adequacy of regulations in addressing legal imbalances to promote contractual justice and balanced relations. Using a normative juridical approach with qualitative analysis of MSME contract regulations, the research assesses fairness, balance, and legal protection in partnership practices. Findings reveal most MSMEs lack understanding of contract clauses and face weak bargaining power against larger partners. This imbalance worsens due to insufficient legal protection and enforcement. Current regulations remain largely normative and fail to effectively oversee partnership practices. The study recommends legal training and support for MSMEs, alongside policy reforms that ensure contractual fairness, including standardized agreements, independent monitoring, and strict sanctions against dominant large businesses abusing their position. . Keywords: Effectiveness, Contract, Clauses, MSMEs